306 Eechocardiographic Findings in Obese Adolescents with and without Asthma - Montejano-Elías, Lizette (World Allergy Organization Journal, 2012)
BACKGROUND: To detect echocardiographic alterations in the diameter of the aorta in relation to the diameter and ventricular volume in obese adolescents with or without intermittent asthma as well as in eutrophic adolescents with or without asthma. METHODS: Cross-sectional, prospective study in 10 to 17 year old adolescents. They were stratified into 4 groups based on the intermittent asthma diagnosis (GINA classification) and in the Body Mass Index [BMI] (Obesity: BMI higher than the percentile 95%; eutrophic: BMI percentile 10 to 85% according to CDC). Anthropometry and echocardiogram tests were done on all adolescents. Measures of central tendency were obtained (mean and 95% confidence interval [CI]) and data were analyzed through corrected ANOVA post HOC. RESULTS: One hundred and ninety-four subjects were studied and divided into 4 groups: obese with intermittent asthma (OA) [N = 72], obese without asthma (OnA) [N = 73], eutrophics with intermittent asthma (EA) [N = 22], eutrophics without asthma (EnA) [N = 27]. Expressing the mean values and the 95% CI, we obtained the relation of the aorta with the left ventricular diastolic diameter indexed to the body surface (millimeters [mm]) in OA = 1.105 (1.047–1.164), OnA = 1.130 (1.06–1.192), EA = 0.921 (0.885–0.988), EnA = 0.967 (0.873–1.061) [P < 0.05 EA vs OA y OnA]. For the aorta in relation to the left ventricular diastolic volume in mm/milliliters [mL] the values were: OA = 0.648, (0.624–0.673), OnA = 0.645 (0.623–0.666), EA = 0.649 (0.620–0.679), EnA = 0.650 (0.615–0.684) [P > 0.05]. The aorta values in relation to the stroke volume [mm/mL] were: AO = 0.573 (0.530–0.617), OnA = 0.553 (0.511–0.594), EA = 0.596 (0.526–0.666), EnA = 0.595 (0.525–0.665) [P > 0.05]. CONCLUSIONS: The diameter of the aorta in relation to the left ventricular diastolic diameter was lower in eutrophic adolescents with intermittent asthma. There was no difference in the diameter of the aorta of the obese adolescents with and without intermittent asthma.